Growing Food, Products, and Businesses : Applying Business Incubation to Agribusiness SMEs - infoDev (World Bank, Washington, DC, 2015)
The report is organized into nine chapters. Chapter one provides the introduction to the report. Chapter two presents alternative approaches to agribusiness development and chapter three discusses the role of agribusiness incubators. Chapter four discusses the challenges of agribusiness incubators and chapter five presents a typology of agribusiness incubators. Chapter six elaborates on the evolution of incubators over time. Chapter seven presents the analysis of impact and cost-benefits. Chapter eight summarizes good practices and lessons learned. Chapter nine presents the recommendations.